A bibliometric analysis of publications in 3D printing in surgery from the web of science database - Bitesh Kumar; Anjan Kumar Dhua; Mohit Garg; Vishesh Jain; Devendra Kumar Yadav; Prabudh Goel; Sachit Anand; Divya Jain (Annals of 3D Printed Medicine)
Background: Three-dimensional (3D) printing technology, introduced by Charles Hull in 1986, has revolutionized prototyping and is increasingly applied in medical fields such as orthopedics, neurosurgery, and cardiac surgery. The technology offers numerous benefits, including reduced surgical complications, cost-effectiveness, and customization of medical devices. This study provides a bibliometric analysis of 3D printing in surgery, highlighting trends, influential countries, and key research contributors. Objectives: This study aims to analyze the publication landscape of 3D printing in surgery, focusing on key metrics such as annual citation rates, growth trends, citation per year, total citations, source journals, author details, country-wise production, and institutional contributions. The study also aims to explore collaborative patterns at the author, institutional, and country levels and identify core research areas through keyword co-occurrence analysis. Materials and Methods: Data were collected from the Web of Science (WoS) Core Collection on August 13, 2023, including documents published from 2001 to 2022. A total of 3,230 documents were identified and analyzed using VOSviewer and the Bibliometrix R-package. Inclusion criteria encompassed English-language documents related to 3D printing in surgery, while documents published after December 2022 were excluded. Results: The analysis revealed a significant annual growth rate of 20.08 % in publications related to 3D printing in surgery, with peak years being 2022, 2021, and 2020. China and the USA dominate the research output, accounting for approximately 50 % of global publications. Shanghai Jiao Tong University and Sichuan University are leading institutions. Collaborative patterns show strong author linkages and international cooperation, particularly between the USA, China, and England. Keyword co-occurrence analysis identified ''reconstruction,'' ''accuracy,'' and ''additive manufacturing'' as core research areas. Conclusion: This bibliometric analysis provides a comprehensive overview of the research landscape of 3D printing in surgery, emphasizing this technology's rapid growth and significant impact. The insights gained can guide future research, foster collaborations, and inform policy decisions to advance the field. Leading countries and institutions are crucial in driving scientific discoveries and translating research into clinical practice.